The Activities of the Mobilizing Teacher Program on Improving the Pedagogic Competence of Elementary School Mobilizing Teachers - Ratna Hayu; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi; Sri Untari (LPPM Undiksha, 2024)
Some teachers still need help understanding the new curriculum, namely independent learning. Through the teacher mobilization program, teachers need to continue developing themselves and improving their competencies to respond to these challenges well. This research aims to analyze the influence of the driving teacher program activities on increasing the pedagogical competence of driving teachers in elementary schools. This research uses quantitative research, survey methods and a correlational approach. The population and sample of this research is 30 people. This research was conducted using data collection techniques in the form of questionnaires. The techniques used to analyze data are quantitative descriptive analysis and inferential statistical analysis. The results of this research show a significant relationship between the activities of the driving teacher program and increasing the pedagogical competence of elementary school-level driving teachers. The correlation coefficient value of 0.823 indicates a strong relationship between the two variables. Simple linear regression analysis shows that the driving teacher program activities have a significant influence on increasing the pedagogical competence of driving teachers. Every one-unit increase in teacher mobilization program activities contributes to increasing pedagogical competence. It was concluded that the driving teacher program activities could increase the pedagogical competence of elementary school-level driving teachers.